The prophet Enoch among the Maya of the Yucatan Peninsula - Paul Sullivan (Journal de la Société des Américanistes)
Mayas in Yucatan and Quintana Roo, Mexico, tell stories of having been visited by a prophet of the apocalypse who called himself Enoch. This article relates the content of those stories, reveals the identity of the alleged prophet, and explores how Mayas shaped a quixotic figure from the 1920s into a divine messenger endowed with attributes drawn from Maya mythologies.